EU Economic Sanctions and Their Impact on The Performance of Russian Companies - Anatol MELEGA; Veronica GROSU; Anamaria - Geanina MACOVEI; Mihaela TULVINSCHI (Communications of International Proceedings, 2022)
The current global instability of the political, economic and health domains has negative repercussions on business development and foreign direct investments. Russia, one of the largest recipients of foreign capital, has attracted a series of sanctions from major economic partners such as the European Union following the invasion of Ukraine. EU economic sanctions on Russia began in 2014 when Russia annexed Crimea, subsequently easing against the backdrop of peace deals, and in February 2022 with Russia's attempt to annex other territories in Ukraine, several EU and non-EU member states condemned the invasion by imposing economic sanctions and even severing political partnerships. The purpose of this research is to analyse the effects of economic sanctions on the performance of Russian firms. Through this research we aim to highlight the importance of sustainable economic relations between states in the economic and social well-being of the business environment and society.
Keywords: crisis; economic sustainability; economic restrictions; firm performance.